The degree of bother and healthcare seeking behaviour in women with symptoms of pelvic organ prolapse from a developing gulf country - Fayez T. Hammad; Hassan M. Elbiss; Nawal Osman (BMC, 2018)
Abstract Background The healthcare-seeking behaviour of women with pelvic organ prolapse (POP) is affected by several factors including the cultural background. There is limited number of studies which addressed the healthcare-seeking behaviour in women with POP. The aim of this study was to determine the degree of bother, social impact and healthcare seeking behaviour of symptoms of POP in one of the Gulf countries and compare the results to published data from other areas. Methods All women who attended the three family development centres in our city between January 2010 and January 2011 and who had symptoms suggestive of POP were included in the study. The data was collected by well-trained interviewers. Results One hundred twenty-seven women reported symptoms of POP (mean age: 38.2 years; range: 18-71). Out of these, 111 (87.4%) had at least one activity (physical, social or prayers) or sexual relationship affected by POP symptoms. In 49 women (38%), the effect on at least one of these activities or relationships has been described as moderate and in 18 women (14%), the effect was severe. Sixty-nine women (54%) did not seek medical advice due to: embarrassment to see medical doctors (51%), the belief that POP is normal among women (51%), hope for spontaneous resolution (48%), embarrassment to see male doctors (33%) and unawareness of the existence of medical treatment (30%). On univariate analysis, the need to insert the finger in the vagina to empty the bladder or bowel and the interference of symptoms with physical activities, had significantly determined healthcare seeking attitude (P < 0.05 for all). However, on multivariate analysis interference with physical activities was the only significant determinant (P = 0.04). Conclusions Although POP had affected the quality of life in the majority of the affected women, unlike some other societies, more than half failed to seek healthcare advice mainly due to shyness and embarrassment and lack of proper knowledge about the condition. Interference of symptoms with physical activities was the main significant determinants of healthcare-seeking behaviour. Additional teaching campaigns designed according to cultural backgrounds in each society are required to address these sensitive issues.